PENGARUH PESAN DAKWAH PADA CHANNEL YOUTUBE SHIFT MEDIA TERHADAP PERILAKU BERAGAMA REMAJA MUSLIM CITAYAM DEPOK - Khoirun Nisa; Chodidjah Makarim; Gunawan Ikhtiono (KOLONI, 2023)
Social media is one of the most widely used media, with the ease of access that is obtained making people often use it anytime and anywhere, one of which is YouTube. YouTube is social media that is now being used as a media for preaching. The method of preaching through the YouTube channel has a great opportunity to help convey the message of da’wah. Many preachers use YouTube to preach, one of which is the Shift Media channel. This account always uploads content that contains da’wah messages that target teenagers and invite goodness. This study used a survey method with data collection techniques using a questionnaire in the form of a Google form given to 100 respondents. And the purpose of this study is to find out what most influences the religious behavior of Citayam Depok Muslim youth from the three variables of tabligh indicators, advice indicators, and amar ma’ruf nahi munkar indicators. In order to provide knowledge and benefits to the community. This research approach uses quantitative primary data types with independent variables in the form of tabligh, advice, and amar ma’ruf nahi munkar and the dependent variable in the form of religious behavior. This study used validity and reliability tests, then used the Kolmogorov Smirnov normality test, and used the Coefficients T test, Model Summary test, multiple regression test, and hypothesis testing. The results of thid study obtained an F significance of 0,001 < 0,05 which means that there is a simultaneous influence of da’wah messages on the religious behavior of Citayam Depok Muslim Youth and the results of the Summary Model test show that power that influences X1, X2, and X3 on Y is equal to 0,688 or 68,8% obtained the results if the T test that there was no significant effect on the tabligh and advice variables but there was a significant effect on the amar ma’ruf nahi munkar variable on religious behavior with a value of 0,001 < 0,05 or T count 4,532 which means > from the T table value 0f 1,984 then Ho is accepted and Ha is rejected. This shows that the variable that is very dominant in influencing the religious behavior of Citayam Depok Muslim youth is the amar ma’ruf nahi munkar variable Keywords: influence, da’wah messages, religious behavior, youth